Pregnancy-Related Stress Among Pregnant Women Receiving Tocolytic and Non-Tocolytic Treatments Where Both Used Complementary Medicine - Hsu, Chen-Yuan; Chen, Ching-Li; Tsai, Li-Yun; Tsai, Jung-Mei (Frontiers in Pharmacology, 2022)
Objective: This study aimed to compare the pregnancy stress between pregnant women who both used complementary medicine in receiving with tocolytic and non-tocolytic treatment. Methods: A cross-sectional survey was conducted among 35 pregnant women receiving with tocolytic and 35 were non-tocolytic treatment who both used complementary medicine in a medical center in central Taiwan. A basic information questionnaire that contained demographic variables and types of complementary medicine used, and the Pregnancy Stress Rating Scale were used for the analysis. Results: The types of complementary medicine were surveyed using the multiple-choice questionnaire. Natural products (77.5%) were most commonly used by pregnant women receiving with tocolytic, followed by alternative medicine (13.75%), manipulative and body-based practices (5%), and mind and body medicine (3.75%). In pregnant women who were non-tocolytic treatment, natural products (59.1%) were most commonly used, followed by manipulative and body-based practices (16.4%), alternative medicine (15.4%), mind and body medicine (7.3%), and energy therapy (1.8%). According to analysis of covariance test results, while both used complementary medicine in groups, pregnant women receiving with tocolytic who were less stressed than those who were non-tocolytic treatment (Pregnancy Stress Rating Scale score, p =0 .038), especially in dimension 2 (stress caused by infant care and changes in family relationships) (p = 0.015), and dimension 5 (stress caused by changes in physical appearance and function) (p = 0.008), which showed statistically significant differences (p <0.05). Linear regression analyses results showed that gestational age significantly associated pregnancy stress (Pregnancy Stress Rating Scale score, p =0.029; dimension 2, p =0.016; and dimension 5, p =0.001). Conclusions: Both used complementary medicine, pregnancy stress was significantly lower in pregnant women who receiving tocolytic than those pregnant women who were non-tocolytic treatment. This finding can be used as a reference for future pregnant women's health studies.